2008
DOI: 10.1080/15374410801955896
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Penn State Worry Questionnaire for Children in a Large Clinical Sample

Abstract: The Penn State Worry Questionnaire for Children (PSWQ-C; Chorpita, Tracey, Brown, Collica, & Barlow, 1997) is a 14-item self-report measure of worry in children and adolescents. Although the PSWQ-C has demonstrated favorable psychometric properties in small clinical and large community samples, this study represents the first psychometric evaluation of the PSWQ-C in a large clinical sample (N = 491). Factor analysis indicated a two-factor structure, in contrast to all previously published findings on the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 11 publications
5
67
2
Order By: Relevance
“…PSWQ-C scores can range between 0 and 42, with higher scores indicating greater levels of worry. The psychometric properties of the PSWQ-C are adequate both in community and in clinical samples [9,[11][12][13][14][15]. Internal consistency coefficients range from .82 [14] to .91 [15].…”
Section: Introductionmentioning
confidence: 91%
“…PSWQ-C scores can range between 0 and 42, with higher scores indicating greater levels of worry. The psychometric properties of the PSWQ-C are adequate both in community and in clinical samples [9,[11][12][13][14][15]. Internal consistency coefficients range from .82 [14] to .91 [15].…”
Section: Introductionmentioning
confidence: 91%
“…Hazlett-Stevens et al(2004) demonstrated a weak correlation between the five-reviseditem factor and GAD, which was measured by a self-reported questionnaire. However, Pestle et al (2008) found that, in the study of the PSWQ for children, the reverse-scored items can predict the variability in clinician-reported ratings of generalized anxiety, but not self-reported anxiety. This implies that the revised items, Factor 2, may have an independent role, distinct from Factor 1 of the PSWQ.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the mean self-reported worry in the current sample was more analogous to that previously found in a clinical sample (Pestle, Chorpita, & Schiffman, 2008). These findings were consistent with Silverman and colleagues (1995) who found that African American children reported more worries than their non-Hispanic White and Hispanic counterparts, particularly in the areas of personal harm, family, and war.…”
Section: Preliminary Analysessupporting
confidence: 82%
“…Validity analyses of the PSWQ-C have found this measure to be significantly convergent with related constructs, including GAD diagnosis, self-reported GAD symptoms, depression, self-reported anxious symptoms, and negative affect (Chorpita et al, 1997;Esbjorn et al, 2013;Muris et al, 2001;Pestle et al, 2008). Internal consistency was good in the current sample (α= .85).…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation